Sustainability Strategy for Agricultural Reform in Mekarsari Village, Panimbang District, Pandeglang - Achmad Syarif Hidayatulloh Ali; Endriatmo Soertarto; Lukman M Baga (Budapest International Research and Critics University, 2022)
Inequality of land tenure and poverty are two currencies that cannot be separated. This is caused by injustice in gaining access to control and utilizing agrarian resources, especially for the poor. Agrarian reform is one solution to the problem of inequality and injustice. Agrarian reform includes asset management and access arrangements. The implementation of agrarian reform in Mekarsari Village was carried out in 2018 through a land consolidation mechanism and the formation of an agrarian reform village. This study aims to analyze the factors that influence the implementation of agrarian reform in Mekarsari Village and formulate strategies that can be implemented so that the agrarian reform village can be sustainable. The analysis used is the IFE, EFE, IE, SWOT matrix and the strategy architecture. The results showed that 8 internal and external factors influenced the implementation of agrarian reform. The results of the IE matrix analysis are in quadrant I with a growth and development strategy. The SWOT analysis produces 11 alternative strategies, which are then compiled through a strategic architectural approach that has a road map to a sustainable agrarian reform village.